PREVALENCE OF UPPER CROSS SYNDROME IN WORKING FEMALE PHYSIOTHERAPISTS: A CROSS-SECTIONAL SURVEY - HUSSAIN , G; NAWAZ , AS; HAROON , MS; AMON, .; SOHAIL , K; KHAN , H (Biological and Clinical Sciences Research Journal, 2023)
Upper crossing syndrome is a common postural dysfunction resulting from the muscles in the body's shoulder girdle/cervicothoracic region having a deficient tone. The muscles typically affected are the upper trapezius and the levator scapula, which is extremely common in physiotherapists. Poor posture is the main driver of UCS. Researchers have long seen the syndrome, whose work demands much bending and twisting. A cross-sectional study assessed the Upper Cross Syndrome in working female physiotherapists. Two hundred female physiotherapists completed The Oswestry Neck Pain and Disability Questionnaire, administered to individuals aged 23-38 who met the inclusion and exclusion criteria. Significant factors for the prevalence of upper cross syndrome in female physiotherapists were Age, gender, and working hours, all of which posed serious risks for the emergence of UCS. UCS was, nevertheless, very common among female physiotherapists. It was determined that 27% of practicing physiotherapists had Upper Cross Syndrome (UCS). The study found that pain intensity, headache, driving, and work were all significantly associated, with P-values of 0.000, 0.005, and 0.002, respectively, as determined by the chi-square test. This indicates that the results were statistically significant. Additionally, the study revealed that upper cross syndrome was highly prevalent among working physiotherapists, with a prevalence rate of 27%. The prevalence was directly related to the duration and hours of work. Furthermore, there was a strong correlation between work-related musculoskeletal disorders and upper cross syndrome.